Solution-processed inverted organic solar cell using V2O5 hole transport layer and vacuum free EGaIn anode - Ongul, Fatih (ELSEVIER, 2015)
In this study, the sol-gel V2O5 derived by a hydrothermal method to replace the PEDOT:PSS which is a hole transport layer between organic active layer and two different anodes in inverted organic solar cells with TiO2 as. an electron transport layer was investigated. The power conversion efficiencies of inverted Organic photovoltaic cells increased approximately twofold with using V2O5 instead of PEDOT:PSS on top of the photoactive layer. It was demonstrated that the power conversion efficiencies of inverted organic solar cells prepared with V2O5 solution which was diluted with isopropanol in certain proportions by volume were decreased by increasing ratio of isopropanol in total volume. It was reported for the first time that the inverted organic photovoltaic cells prepared using V2O5 interlayer and Eutectic Gallium-Indium alloy which was prepared using vacuum free simple brush-painted method and can be used as anode electrode as Ag electrode. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: EGaIn; V2O5; Vacuum free; Inverted OPV; BULK-HETEROJUNCTION; BUFFER LAYER; EXTRACTION; LIGHT; DEGRADATION; PERFORMANCE; EFFICIENT; ELECTRON; OXIDE; Materials Science; Optics